2008
DOI: 10.1577/m06-033.1
|View full text |Cite
|
Sign up to set email alerts
|

Gape: Body Size Relationship of Flathead Catfish

Abstract: The flathead catfish Pylodictis olivaris is a highly piscivorous ictalurid native to central North America whose range has been extended throughout much of the United States. With this range expansion, many populations of native fishes have experienced declines in the number of individuals due to direct predation by flathead catfish. Previous evidence suggests that flathead catfish are opportunistic feeders and may be the least gape limited of North American freshwater piscivores. To better understand the size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The primary alosine consumed by Flathead Catfish was Blueback Herring, which was found in nearly 10% of stomachs; Flathead Catfish also consumed American Shad and Alewives but to a lesser degree. Even small Flathead Catfish were piscivorous; this is likely mediated by their huge gape size, which is among the largest observed in any North American freshwater fish species (Slaughter and Jacobson 2008). Because of their voracious feeding habits, Flathead Catfish are already considered to be one of the most ecologically harmful introduced species in the United States (Fuller et al 1999), and several studies have empirically demonstrated declines in native fish populations after the introduction of Flathead Catfish (Guier et al 1984;Ashley and Buff 1988;Thomas 1995;Kwak et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The primary alosine consumed by Flathead Catfish was Blueback Herring, which was found in nearly 10% of stomachs; Flathead Catfish also consumed American Shad and Alewives but to a lesser degree. Even small Flathead Catfish were piscivorous; this is likely mediated by their huge gape size, which is among the largest observed in any North American freshwater fish species (Slaughter and Jacobson 2008). Because of their voracious feeding habits, Flathead Catfish are already considered to be one of the most ecologically harmful introduced species in the United States (Fuller et al 1999), and several studies have empirically demonstrated declines in native fish populations after the introduction of Flathead Catfish (Guier et al 1984;Ashley and Buff 1988;Thomas 1995;Kwak et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, Flathead Catfish appeared capable of passing the notched dam under all flow conditions, suggesting their downstream delays may be a choice (e.g., foraging) rather than forced. Flathead Catfish have the potential to negatively impact native fishes as their large gape size allows them to consume adult American Shad, Gizzard Shad, Largemouth Bass, and Bluegills (Ashley and Buff 1988;Pine et al 2005;Slaughter and Jacobson 2008).…”
Section: Notched Dam Passage and Delaymentioning
confidence: 99%
“…Prey selected by a predator depends on the characteristics expressed by both predator and prey, and how these interact (Cohen et al 1993, Woodward et al 2005, Urban 2007). For many piscivores, the upper limit of potential prey sizes is set by morphological constraints imposed by mouth width, or gape size (a mechanism known as 'gape-limitation'; Persson et al 1996, Slaughter & Jacobson 2008. According to OFT, as predator size increases, the optimal prey size on which to feed should also increase (Hughes 1980).…”
Section: Abstract: Predation · Selection · Body Size · Gape Limitatimentioning
confidence: 99%